Optimization and evaluation of precision distribution of loaned instruments and implants for orthopedic surgery (骨科外来器械及植入物精准配送的流程优化与效果评价) - XIA Yesong (夏叶松); ZOU Xiufang (邹秀芳); FU Chaojuan (付朝娟) (Association of Integrative Nursing, 2022)
Objective To optimize and evaluate the precision distribution of loaned instruments and implants for orthopedic surgery. Methods Distribution process of loaned instruments and implants for orthopedic surgery was optimized by interventions such as classification of loaned instruments package, "packaging-coding-sterilization-tracing-charging" management circle, point-to-point distribution and so on. Totally 90 patients undergoing lumbar pedicle screw fixation between March and June 2019 (before implementation of process optimization ) were selected as the control group, another 89 patients undergoing lumbar pedicle screw fixation between March and June 2021 (after implementation of process optimization ) were selected as the observation group. The time cost in checking loaned surgical instruments, wrong charging fee for implants and medical dispute event were observed and analyzed retrospectively. The surgical nurses' satisfaction with distribution of loaned instruments and implants for orthopedic surgery was evaluated. Results The averaged time cost in checking loaned surgical instruments in the observation group was (283. 70±24. 55) s, which was lower than (732. 06±43. 06) s in the control group (P＜0. 05). Three cases of wrong charging fee for implants and 2 cases of medical dispute events were reported in the control group. The satisfaction rates with distribution of loaned instruments and implants were higher in the observation group than those in the control group (P＜0. 05). Conclusion Process optimization of loaned instruments and implants for orthopedic surgery is effective to improve the checking efficacy and standardize the charging fee for implants, reducing workload of surgical nurses and ensure the safety high-efficient surgery. (目的 探讨骨科外来器械及植入物精准配送的流程优化与效果。方法 对骨科外来器械及植入物精准配送的流程进行优化, 如外来器械包精简分类、植入物采用"一物一码一灭菌一追溯一计费"、点对点配送等。选取2019年3月-6月于本院行腰椎椎弓钉螺钉内固定术的91例患者为对照组(流程优化前), 另选取2021年3月-6月行腰椎椎弓钉螺钉内固定术的89例患者为观察组(流程优化后)。记录2组骨科器械清点消耗时长、植入物计费错误及医疗纠纷发生情况, 比较手术室护士对2组外来器械及植入物配送工作的满意度。结果 观察组器械清点消耗时长为(283. 70±24. 55) s/台, 短于对照组(732. 06±43. 06) s/台, 差异有统计学意义(P＜0. 05)。观察组未发生植入物计费错误以及医疗纠纷。对照组发生3例植入物计费错误和2例医疗纠纷。手术室护士对观察组外来器械及植入物配送工作的满意度高于对照组, 差异有统计学意义(P＜0. 05)。结论 对骨科外来器械及植入物精准配送的流程进行优化, 能提高手术室护士器械清点效率, 规范植入物精准计费, 减轻手术室护士的工作量, 确保骨科手术安全且高效运行, 具有一定护理工作指导意义。)